1979
DOI: 10.1029/rg017i008p02049
|View full text |Cite
|
Sign up to set email alerts
|

Inductive electric fields in the Ionosphere‐Magnetosphere System

Abstract: In recent years, there has been increasing awareness of the importance of large‐scale electric fields in the earth's magnetosphere. Much attention has been directed to the quasi‐static electric field associated with charge separations generated by solar wind‐magnetosphere interaction, but these seem inadequate to explain many important processes. This paper reviews the evidence for the inclusion of electric fields of inductive origin, i.e., those due to time‐dependent currents in the magnetosphere‐ionosphere s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…There are still open questions regarding this process, especially, for storm times, such as, whether substorm-associated magnetic field variations and the associated (inductive) electric fields are necessary for the buildup of the ring current energy density. While there are arguments that large-scale convection alone can account for the ring current increase, other studies have concluded that energization of ring current particles to energies over 100 keV requires smaller-scale, timevarying electric fields (see one of the earliest studies on this subject by Kim et al 1979 and more recent reviews by Daglis and Kozyra 2002;Ebihara and Ejiri 2003;Kozyra and Liemohn 2003;Ebihara and Miyoshi 2011;Bourdarie et al 2016;Ebihara 2016 and references therein).…”
Section: Ring Current In the Earth's Magnetosphere: Brief Reviewmentioning
confidence: 99%
“…There are still open questions regarding this process, especially, for storm times, such as, whether substorm-associated magnetic field variations and the associated (inductive) electric fields are necessary for the buildup of the ring current energy density. While there are arguments that large-scale convection alone can account for the ring current increase, other studies have concluded that energization of ring current particles to energies over 100 keV requires smaller-scale, timevarying electric fields (see one of the earliest studies on this subject by Kim et al 1979 and more recent reviews by Daglis and Kozyra 2002;Ebihara and Ejiri 2003;Kozyra and Liemohn 2003;Ebihara and Miyoshi 2011;Bourdarie et al 2016;Ebihara 2016 and references therein).…”
Section: Ring Current In the Earth's Magnetosphere: Brief Reviewmentioning
confidence: 99%
“…Due to the difference in ion and electron mobility, charge separation generates the static ionospheric electric field. This field is further influenced by the timedependent electric field of inductive origin associated with magnetosphere-ionosphere currents [12]. Thus, this field is influenced by various factors such as solar wind, Earth's magnetic field, and atmospheric winds.…”
Section: Introductionmentioning
confidence: 99%